Knowledge Spillovers from Creation to Exploitation: A Theoretical Model with Implications for Firms and Public Policy - Z. Acs; Claire Economidou; Mark Sanders (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
In this paper we present an endogenous growth model in which we investigate the implications of knowledge spillovers between knowledge creators (inventors) and commercializers (innovators). We then turn to the question how such knowledge spillovers affect value creation within and among organizations as well as at the aggregate level and discuss how the internalization of these knowledge spillovers can help improve economic performance at both levels.
Keywords: 330; knowledge spillovers; innovation management; strategic entrepreneurship